2017
DOI: 10.1002/cssc.201701538
|View full text |Cite
|
Sign up to set email alerts
|

Level Alignment as Descriptor for Semiconductor/Catalyst Systems in Water Splitting: The Case of Hematite/Cobalt Hexacyanoferrate Photoanodes

Abstract: The realization of artificial photosynthesis may depend on the efficient integration of photoactive semiconductors and catalysts to promote photoelectrochemical water splitting. Many efforts are currently devoted to the processing of multicomponent anodes and cathodes in the search for appropriate synergy between light absorbers and active catalysts. No single material appears to combine both features. Many experimental parameters are key to achieve the needed synergy between both systems, without clear protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 71 publications
2
51
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19] Although the use of robust heterogeneous assemblies such as oxides could be apromising solution to improve stability,the lack of complete control on the coordination of metal ions in oxide chemistry does not allow the preparation of oxidebased dyads. [22][23][24][25][26][27][28][29][30][31] PBAs consist of earth-abundant elements,perform at relatively low overpotentials (< 500 mV for ac urrent density of 1mAcm À2 ), exhibit exceptional stabilities in awide pH range (from 1to13), and can operate even with molecular chromophores for light-driven catalysis. [21] Different perspectives of cobalt-based Prussian blue analogues (PBAs) as WOCs have recently been explored by us and other researchers.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Although the use of robust heterogeneous assemblies such as oxides could be apromising solution to improve stability,the lack of complete control on the coordination of metal ions in oxide chemistry does not allow the preparation of oxidebased dyads. [22][23][24][25][26][27][28][29][30][31] PBAs consist of earth-abundant elements,perform at relatively low overpotentials (< 500 mV for ac urrent density of 1mAcm À2 ), exhibit exceptional stabilities in awide pH range (from 1to13), and can operate even with molecular chromophores for light-driven catalysis. [21] Different perspectives of cobalt-based Prussian blue analogues (PBAs) as WOCs have recently been explored by us and other researchers.…”
mentioning
confidence: 99%
“…Even for CoFe‐PBAs, their integration gave rise to different results depending on the type of an underlying photoanode (Figure c). While there was a significant performance improvement for BiVO 4 , there was a negligible improvement for Fe 2 O 3 (Figure c‐d) due to the undesirable alignment of the VB of Fe 2 O 3 and t 2g level of Co in CoFe‐PBAs for efficient charge transport (Figure e) , . In addition, it is reported that PBA‐modified photoanodes exhibit excellent photochemical stability due to their additional role as a protective coating layer , .…”
Section: Self‐assembly and Surface Precipitation Of Precursors Formentioning
confidence: 95%
“…While there was a significant performance improvement for BiVO 4 , there was a negligible improvement for Fe 2 O 3 (Figure c‐d) due to the undesirable alignment of the VB of Fe 2 O 3 and t 2g level of Co in CoFe‐PBAs for efficient charge transport (Figure e) , . In addition, it is reported that PBA‐modified photoanodes exhibit excellent photochemical stability due to their additional role as a protective coating layer , . Despite their interesting and promising properties, however, their application in photocatalytic water oxidation seems to still be in its infancy, as evidenced by the utilization of only Co‐based PBAs.…”
Section: Self‐assembly and Surface Precipitation Of Precursors Formentioning
confidence: 99%
See 2 more Smart Citations